Effect of Transglutaminase Enzyme on Physico-mechanical Properties of Rambouillet Wool Fiber. Issue 6 (2nd June 2020) - Soun, Bhawna; Kaur, Devinder; Jose, Seiko
ABSTRACT: Rambouillet wool fiber was scoured and treated with transglutaminase (TG) enzyme for different concentrations and duration at neutral pH at 45°C. The physical, mechanical, dyeing, and antimicrobial properties of the wool fiber before and after enzymatic treatment were evaluated as per standard methods. Results inferred that TG enzyme-treated wool fiber sample showed improvement in softness, luster, and tensile strength in comparison with scoured wool fiber. It is found that 0.5% TG enzyme treatment at 45°C for 60 min at pH 7 was an optimum condition. Scanning electron microscope images also confirmed the flattened and smooth scales of wool fiber after enzymatic treatment.